Physicochemical, spectral, medicinal, and toxicological studies of Ketoprofen, Ibuprofen, and their major degradants: A quantum-chemical and in silico approach - Protyoi Chakraborty; Saithajit Mohajan; Omme Samia; Nusrat Jahan; Nazmul Islam; Mahbub Alam; Monir Uzzaman (PLoS ONE, 2026)
Nonsteroidal Anti-inflammatory drugs (NSAIDs) are significantly consumed all over the world to treat pain, inflammation, and fever. Despite their ability to reduce pain and inflammation, they and their degradants can be toxic to both human organisms and the environment. This in-silico investigation has examined the spectral, physicochemical, biological, and toxicological properties of two frequently used NSAIDs, Ketoprofen (KTP) and Ibuprofen (IBP), along with some of their major degradants. Here, we have employed density functional theory, with the B3LYP/6-31g+(d,p) basis set, to determine the physicochemical as well as spectral properties of these compounds. Additionally, we have employed several computational methods to assess their biological and toxicological properties. We also executed molecular docking and nonbonding interaction calculations to investigate their binding properties and mode(s) of action against the Aspirin Acetylated Human Cyclooxygenase-2 receptor (PDB ID: 5F19), along with MD simulation of these complexes. 2-(4 methylphenyl) propanoic acid (IBP6), showed the greatest values of enthalpy and free energy, whereas 2-hydroxy Ibuprofen (IBP5) showed the highest binding interactions. For HOMO-LUMO values, 2-(3-(2-hydroxy-3-methylbenzoyl)phenyl) propanoic acid (KTP1) shows the lowest gap of 3.806 eV and 1-(4-isobutylphenyl) ethanol (IBP2) shows the highest gap of 6.063 eV. In case of binding affinity, 2-(3-(3- hydroxybenzoyl)phenyl) propanoic acid (KTP2) showed the highest value whereas, 3-hydroxy-carboxymethyl hydratopic acid (KTP3) and 2(-(4-formylphenyl) propanoic acid (IBP4) illustrated the lowest values of binding affinity. Additionally, ADMET and PASS predictions were evaluated to compare their biological and toxicological parameters. The investigated complexes illustrated constancy over a 100-ns MD simulation, demonstrating crucial hydrogen bonding. Several of these degradants have demonstrated carcinogenic, nephrotoxic, and hematotoxic properties, which highlight their toxicological impact on human organisms. This investigative study can help raise awareness about the toxicological impacts of these drugs and their degradants on the environment as well as human health.